Eosinophils, Stroke-Associated Pneumonia, and Outcome After Mechanical Thrombectomy for Acute Ischemic Stroke - Guo, Zhiliang; Hou, Jie; Yu, Shuai; Zhang, Hang; Yu, Shuhong; Wang, Huaishun; Xu, Jiaping; You, Shoujiang; Huang, Zhichao; Xiao, Guodong; Cao, Yongjun; Liu, Chun-Feng (Frontiers in Aging Neuroscience, 2022)
Background: Eosinophils contribute to antibacterial defense by releasing mitochondrial DNA, which are decreased in patients with acute ischemic stroke (AIS). However, the impact of eosinophils on stroke-associated pneumonia (SAP) among AIS patients remains unclear. Moreover, whether SAP is in the path of the association between eosinophils and clinical outcome also remains unclear.We aimed to assess the relationships between eosinophils, SAP, and clinical outcome after mechanical thrombectomy in patients with AIS. Methods: A total of 328 consecutive patients with AIS who underwent mechanical thrombectomy between May 2017 and March 2021 were analyzed. Their baseline date and peripheral eosinophil counts were recorded on admission. Regression analysis was used to assess the effect of eosinophils on SAP, and its effect on poor outcome defined as modified Rankin Scale score of 3 to 6 at month 3 after admission. Mediation analysis was utilized to assess the proportion of total effect by SAP on the association between eosinophils and poor outcome. Results: Multivariater analysis revealed that eosinophils was independently associated with SAP after adjusting potential confounders (odds ratio, 0.00; 95% CI, 0.00–0.38; P = 0.0267), which is consistent with the result of eosinophils (dichotomous) as a categorical variable (odds ratio, 0.54; 95% CI, 0.31–0.96; P = 0.0342). A non-linear relationship was detected between eosinophils and SAP, whose inflection point was 0.06. Subgroup analyses further confirmed these associations. Eosinophils was also associated with poor outcome (odds ratio, 0.00; 95% CI, 0.00–0.14; P = 0.0124). And mediation analysis found that SAP partially mediated the negative relationship between eosinophils and poor outcome (indirect effect=-0.169; 95%CI: -0.339 – -0.040, P<0.001). Conclusions: Our findings suggested that lower eosinophil level was associated with higher SAP and poorer outcome, and SAP might play an important effect on the association between eosinophils and poor outcome.